Celebrity CEOs and firm innovation investment: Evidence from Chinese-listed companies - Shao, Dong; Lv, Kangyin; Zhao, Shukuan; Wang, Shuang (Frontiers in Psychology, 2022)
In today’s commercial-oriented world, intense social attention makes it easier for CEOs to become celebrities. This social escalation and characteristic change of CEOs into celebrities tend to influence their motivation and behavior, and thus the strategic decisions and results of firms. Despite the significance of recognizing CEOs’ social identity, the impact of celebrity CEOs on innovation strategy remains unknown. Integrating identity and upper echelons theories, this study examines and provides empirical evidence on how celebrity CEOs affect firm innovation investment using data of Chinese listed companies from 2015 to 2020. We argue that celebrity CEOs’ engagement in innovation investment is driven by their motivation for preserving celebrity status. Further, we show that analyst coverage plays a positive moderating role between celebrity CEOs and innovation investment, and the positive effect of celebrity CEOs on innovation investment becomes weaker in state-owned enterprises. This study confirms the important role of CEOs’ specific social identity in firm innovation strategy, which is motivated by celebrity CEOs’ attempt to maintain their established status and reputation. The results expand the research on the influencing factors of firm innovation investment that focus on executives’ social characteristics. They also provide managerial implications for board of directors to recruit and supervise a celebrity CEO.